2000
DOI: 10.1074/jbc.275.1.565
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Apoptotic Pathway Induced by Nerve Growth Factor-mediated TrkA Activation in Medulloblastoma

Abstract: Nerve growth factor (NGF) induces apoptosis in a human medulloblastoma cell line (MED283) engineered to express TrkA (MED283-TrkA) (Muragaki, Y., Chou, T. T., Kaplan, D. R., Trojanowski, J. Q., and Lee, V. M. (1997) J. Neurosci. 17, 530 -542). To dissect the molecular signaling pathway that mediates this novel effect, specific receptor mutations in Trk have been employed. We showed that phosphorylation of tyrosine 490 is required for activation of phosphoinositide 3-OH kinase, whereas phosphorylation of tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 44 publications
6
41
0
1
Order By: Relevance
“…This result is consistent with the reports of Chou et al (61,62) that TrkA-induced medulloblastoma apoptosis is independent of Erk1/2, JNK, and p38 MAPK. Therefore it is possible that TrkA induces a Ras and/or Raf-dependent, but MEK/Erk1/2-independent pathway that would be responsible for TrkA-induced apoptosis, as it has been suggested for MB (61).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result is consistent with the reports of Chou et al (61,62) that TrkA-induced medulloblastoma apoptosis is independent of Erk1/2, JNK, and p38 MAPK. Therefore it is possible that TrkA induces a Ras and/or Raf-dependent, but MEK/Erk1/2-independent pathway that would be responsible for TrkA-induced apoptosis, as it has been suggested for MB (61).…”
Section: Discussionsupporting
confidence: 83%
“…The only difference we observed in the signaling proteins stimulated by these receptors was a much greater enhancement of sustained Erk1/2 phosphorylation by TrkA. However, suppression of MEK/MAPK activity did not inhibit TrkA-mediated cell death, and TrkA did not increase p38 MAPK activity, which occurs in PC12 cells overexpressing TrkA (31,61). This result is consistent with the reports of Chou et al (61,62) that TrkA-induced medulloblastoma apoptosis is independent of Erk1/2, JNK, and p38 MAPK.…”
Section: Discussionmentioning
confidence: 66%
“…NGF application to wild type medulloblastoma cells or to p75 or TrkC expressing cells had no effect on viability. The death effect was inhibited by K-252A, an inhibitor of TrkA phosphorylation; and likewise was abolished in kinase-dead or signaling tyrosine mutants of TrkA, as well as by a dominant-negative Ras inhibitor (Chou et al, 2000). Pomeroy, Segal, and coworkers carried out a detailed study on TrkC effects in medulloblastoma, and showed that NT-3 stimulation induced death of primary tumor cells in culture under serumfree conditions (Kim et al, 1999).…”
Section: Trk-induced Death In Medulloblastoma and Neuroblastoma Cellsmentioning
confidence: 99%
“…The effects of NGF/tropomyosin receptor kinase A (TrkA) in cancer appear to be related to the cell type. For instance, NGF/TrkA induces differentiation, apoptosis, and growth inhibition in neuroblastoma and medulloblastoma (Chou et al ., 2000; Lavenius et al ., 1995; Matsushima and Bogenmann, 1993), and high expression of TrkA is considered a favorable prognostic indicator in neuroblastoma (Nakagawara et al ., 1993). Whereas TrkAI splice variant was found to induce these effects, the TrkAIII splice variant was shown to possess significant oncogenic effects in neuroblastoma (Farina et al ., 2015; Tacconelli et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%